Management of supracondylar femoral fracture with different techniques in dogs: A gross and undecalcified ground section study - Aithal, H P; Singh, G R (The Indian Journal of Animal Sciences, 2012)
In all 20 mongrel dogs of either sex, divided equally in 4 groups, a transverse supracondylar fracture was created in the left femur and were immobilized with cross IM pinning (group A), modified technique of single IM pinning (group B), standard stainless steel plating (group C), and contoured horn plating (group D). All the animals were euthanized on day 90 and the fracture site was subjected to gross, and undecalcified ground sections (photographic enlarged section and tetracycline labelling) studies. The fracture healing was faster and more complete on endosteal side with no clear demarcation of fracture line than periosteal side in most of the animals of 4 groups. The amount of periosteal callus was relatively more in groups B and C. Fracture healing was more faster in groups A and 0, and it was comparable among them; and healing was slowest in group B, indicating that cross IM pinning and horn plating provide more rigid fixation leading to early healing than single IM pinning and standard stainless steel plating.